Lithofacies and alteration of the Hurricane zone, of the Boomerang volcanogenic massive sulphide deposit, Tulks belt, Central Newfoundland, Canada - English, Michelle (Memorial University of Newfoundland, 2019)
The Hurricane zone of the Boomerang volcanogenic massive sulphide (VMS) deposit is part of the VMShosting Cambro-Ordovician Tulks volcanic belt. The Hurricane zone is one of three lenses in the deposit and consists of a sub-horizontal (semi-)massive sulphide lens with combined resources of 55,100 tonnes @ 13.4% Zn, 7.0% Pb, 1.20% Cu, 159.0 g/t Ag, and 2.00 g/t Au. Mineralization is hosted in intermediate to felsic volcaniclastic rocks of the ca. 488 Ma Pats Pond Group (Victoria Lake supergroup) and consists of banded sphalerite, galena, chalcopyrite, and pyrite, which are interpreted to have formed below the seafloor within subseafloor sediments. Four alteration assemblages are identified: intense sericite-quartzpyrite, sericite-quartz-chlorite-pyrite, intense chlorite and chaotic carbonate. Whole-rock lithogeochemistry and short-wave infrared spectroscopy are useful in identifying key elements/element ratios and variations in white mica chemistry/mineralogy associated with each alteration assemblage and are useful vectors to mineralization.